Developing an Outsource Driver Management Application to Improve Cargo Company Operational Efficiency - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This research aims to develop an outsourced driver management application to improve the operational efficiency of cargo companies. The methods include needs analysis, planning, development, and application testing. The results of this research include designing an intuitive user interface, developing an efficient database management system, implementing responsive real-time tracking features, and integrating with other systems. Comprehensive testing was also conducted to ensure the application's quality, performance, and security before the official launch. The contribution of this research is to provide a solution that can improve the operational efficiency of cargo companies in outsourced driver management and provide an optimal user experience in using the application.